Evidence of SARS-CoV-2 Antibodies and RNA on Autopsy Cases in the Pre-Pandemic Period in Milan (Italy) - Lai, Alessia; Tambuzzi, Stefano; Bergna, Annalisa; Battistini, Alessio; Della Ventura, Carla; Galli, Massimo; Zoja, Riccardo; Zehender, Gianguglielmo; Cattaneo, Cristina (Frontiers in Microbiology, 2022)
In this study we analyzed blood samples obtained from 169 cadavers subjected to autopsy from 1st of October 2019 to 27th of March 2020. The presence of anti-SARS-CoV-2 antibodies was searched by lateral flow immunochromatographic assay (LFIA) and ELISA tests and the SARS-CoV-2 RNA was tested in blood and available lung tissues by real-time RT-PCR and droplet digital PCR (ddPCR). Five cases resulted positives at the serological screening for anti-SARS-CoV-2. Three resulted weakly positive for IgM while only one showed strong reactivity for IgG antibodies. The fifth subject (died in December 2019) resulted positive to ELISA test. The detection of SARS-CoV-2 RNA resulted positive only in the blood and lung tissues of such case. These data show that cadaveric blood may be a suitable substrate for the assessment of SARS-CoV-2 infection; moreover, they extend the observations of sporadic cases of SARS-CoV-2 infection in North Italy before the first confirmed cases.